Chicken eggshell effect as bio-filler on mechanical strength and thermal performance of epoxy composite / Rassimi Abdul Ghani - Abdul Ghani, Rassimi (2011)
The performance of the chicken eggshells as filler in epoxy composites was studied. Different sizes with various proportions of the eggshells samples were tested and comparisons were made. The tensile strength and flexural strength were found to be decreased at more than 50% as the eggshells loading applied in the composite sample at 50% by weight percentage. However, the impact strength was found to be increased as the eggshells loading increased which indicated that the eggshells had imparted some rigidity and stiffness to the composite samples. Meanwhile in thermal conductivity test where the conductivity of the samples declined as the eggshell loading increased. In other word, the thermal insulation of the composite increased with the eggshell loading. From the result of water absorption test, the absorptivity was found to be slightly increased as the eggshells loading increased where the absorption percentage of the water was about 3% for all composite samples.